Biological treatment options for eosinophilic asthma, with consideration of markers of eosinophilic inflammation as predictors of treatment efficacy - Aleksandra Niemiec; Olga Branicka; Barbara Rymarczyk; Radosław Gawlik (Alergologia Polska)
Asthma is one of the most common allergic diseases affecting millions of people of all ages worldwide and influencing socioeconomic issues. Asthma, particularly uncontrolled asthma, not only reduces the quality of life but is also a major cause of disability for employment. The current pharmacologic strategy to therapy consists mostly of inhaled glucocorticoids and β-agonists, as well as leukotriene antagonists, long-acting muscarinic antagonists, and oral corticosteroids. However, the conventional therapy may provide insufficient control of severe asthma and may induce a number of adverse effects when used long-term. These limitations prompted the development of targeted biological drugs that inhibit the mediators involved in T helper 2-inflammation, which is linked to the pathogenesis of asthma, such as interleukin 4, 5, 9, 13 and immunoglobulin E. In many individuals, biological treatment provides significant relief and allows for the reduction or elimination of oral corticosteroids without compromising asthma control. However, some patients do not improve to their full potential. The cause of this phenomenon is unknown and requires further investigation.